Preliminary Protein Profile Analysis of the Late Embryonic B-Cell Stages in the Chicken Bursa of Fabricius - Felfoldi, B.; Pharr, G.T.; Pinchuk, L.M.; Cooksey, A.M.; Thaxton, J.P. (International Journal of Poultry Science, 2008)
The bursa of Fabricius serves as a primary lymphoid organ for the development of a diverse repertoire of B-cells. The embryonic bursa is colonized during embryonic days (ED) 8-14 by stem cells expressing the sialyl Lewisx carbohydrate (SLEX). At ED13-15, cells with the SLEX phenotype initiate proliferation leading to the development of the bursal follicle. By ED15-17, a key differentiation event occurs resulting in the onset of repertoire development by immunoglobulin gene-conversion. This differentiation event is defined by a phenotypic transition in cell surface glycosylation from SLEX to a related carbohydrate structure termed Lewisx(LEX). The goal of this study was to identify functional groups of genes in the two stages that might be involved in critical biological processes of proliferation, differentiation, apoptosis and cell adhesion, and explain the observed functional differences. We found that prior to the onset of immunoglobulin gene conversion B-cells express genes related to ephrin receptor signaling, epidermal growth factor receptor (EGFR) signaling and Wnt signaling. B-cells undergoing immunoglobulin gene conversion express genes from TNFR signaling and both stages were found to express members of Wnt signaling, integrin signaling and EGFR signaling pathways. The differentially expressed pathways agree with previous observations, offering explanation to signals leading to proliferation, differentiation and apoptosis in the two B-cell stages.